Sovereign violence ethics and South Korean cinema in the new millennium - Choe, Steve (Film culture in transition, 2016)
While making reference to dozens of films from the first decade of the twenty-first century, 'Sovereign Violence' performs sustained, comprehensive readings of twenty-one of the most well-known contemporary South Korean films directed by eight auteurs: Hong Sang-soo, Im Sang-soo, Gok and Sun Kim, Kim Ji-woon, Kim Ki-duk, Lee Chang-dong, and Park Chan-wook. Drawing from contemporary film theory and philosophy, as well as reviews, filmmaker interviews, and other primary sources, Sovereign Violence argues that their often violent, contentious films pose urgent ethical dilemmas around life in the age of neoliberal globalization and subsequently point toward new modes of social existence